Drug Use among Iranian Drivers Involved in Fatal Car Accidents - Assari, Shervin; Moghani Lankarani, Maryam; Dejman, Masoumeh; Farnia, Marzieh; Alasvand, Ramin; Sehat, Mahmood; Roshanpazooh, Mohsen; Tavakoli, Mahmood; Jafari, Firoozeh; Ahmadi, Khodabakhsh (Frontiers in Psychiatry, 2014)
Background: Although the problem of substance use among drivers is not limited to certain parts of the world, most epidemiological reports on this topic have been published from industrial world. Aim: To investigate pattern of drug use among Iranian drivers who were involved in fatal road accidents. Methods: This study enrolled 51 Iranian adults who were involved in fatal vehicle accidents and were imprisoned thereafter. Data came from a national survey of drug abuse that was done among Iranian prisoners. The survey collected data at the entry to seven prisons in different regions of the country during a 4-month period in 2008. Self-reported lifetime, last year, and last month drug use was measured. Commercial substance screening tests were applied to detect recent substance use (opioids, cannabinoids, methamphetamines, and benzodiazepines). Results: The commercial substance screening test showed three distinct patterns of recent illicit drug use: opioids (37.3%), cannabinoids (2.0%), opioids and cannabinoids (13.7%). 29.4% were also positive for benzodiazepines. The substance use screening test detected 23.5% of participants who had used drugs but did not disclose any substance use. Conclusion: Opioids are the most common illicit drugs being used by Iranian drivers who are involved in fatal car accidents. The high rate of substance use prior to fatal car accidents in Iran advocates for the need for drug use control policies and programs as major strategies for injury prevention in Iran. There is also a need for substance screening among all drivers involved in fatal car accidents in Iran, as more than 20% of users may not disclose substance use.